(untitled) (Journal of the College of Basic Education, 2022)
The research means studying the study of "students’ attitudes in the arts of drawing and their relationship to their technical achievement in the open educational college" Karbala Center specifically with an analytical study aimed at examining the achievement accomplished in drawing in terms of its technical structure and according to what was accomplished by oil works for the academic year (2015/2019) for students of the Department of Art Education In the Karbala Center specifically, in order to access data that were used in the analysis as a qualitative and descriptive approach. The first chapter included a presentation of the research problem and summarized it in the possibility of answering the question "How did the students’ attitudes represent in the art of drawing and what is the aesthetic value achieved from that?" In addition to the periodic importance of counting the distinguished artistic product for students and seeking to activate intellectual, philosophical and aesthetic propositions, as for the second chapter, it went to the theoretical framework and its indicators that would achieve the mechanisms of analysis in the current study within the topics of the first / technical schools and their trends in drawing and second / indications of drawing and its relationship to speech The philosophy of beauty is the third topic / structure of the technical achievement in drawing and art education, while the third chapter came in research procedures and its society consisting of (14) models according to the sample analysis method consisting of (3) only was chosen intentionally and the descriptive approach was adopted in analyzing the content of the works. The fourth chapter includes the most important results and conclusions. Among the results: Drawing is an expression of the convergence of ideas and cultures, and it is a means of communication and language. The fees aimed to record the reality with the smallest details of the sample 3.The drawings are related to the commercial painting industry. 4.There is a rapprochement between what students drew to express the properties of the artistic painting. 5.There is an emphasis on understanding customary and Sunni ethics in Iraqi society.